EFEKTIVITAS PENGGUNAAN METODE PENDIDIK TEMAN SEBAYA DALAM MENINGKATKAN PENGETAHUAN PENCEGAHAN KOMPLIKASI KAKI DIABETES DI PUSKESMAS BANGUNTAPAN 3 BANTUL - Riza Yulina Amry (Jurnal Ilmiah Keperawatan, 2020)
Diabetic foot is a common complication experienced by people with diabetes mellitus. Knowledge of the complications of diabetic foot is necessary to perform self-care properly. Objective: to analyze the effectiveness of peer educator method health education to increase knowledge of diabetes foot complications prevention. Methods: Quasi experimental with pre-post test control group design was used in this study. Peer educator intervention was used in this study on all patients with type 2 diabetes mellitus at Banguntapan 3 Community Health Center Bantul, as many as 30 patients. Sampling using total sampling, the respondents were divided into 2 (15 interventions and 15 controls). The research instrument was a questionnaire of knowledge about the prevention of diabetic foot complications given before and after the intervention, analyzed by using paired t-test. Results: the pretest in the control group was in the moderate category (73.3%) and the intervention group (66.7%). The posttest results of the control group were in the moderate category (66.7%) and an increase in the intervention group (67.7%). Results: Bivariate analysis showed that there was an influence between the control and experimental groups on knowledge of foot care in patients with diabetes using peer method health education with a p-value of 0.006. Conclusion: the peer educator method is proven to be effective in increasing knowledge of the prevention of diabetes foot complications in diabetes mellitus patients in the Banguntapan 3 Community Health Center, Bantul.